2020
DOI: 10.3390/app11010117
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound for Meat Processing: Effects of Salt Reduction and Storage on Meat Quality Parameters

Abstract: Meat samples (Longissimus dorsi) were processed using an ultrasonic (US) probe system (20 kHz) and a US bath (33 kHz), in brine solutions of 15% NaCl or NaCl/KCl. Selected quality parameters, namely hardness (Warner–Bratzler shear force, WBSF), secondary lipid oxidation products (thiobarbituric acid reactive substances, TBARs) and total colour difference (TCD) were analysed at day 0 and day 60. Inoculated E. coli and L. innocua cells, total viable counts and lactic acid bacteria were also monitored for 60 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 56 publications
(87 reference statements)
0
13
0
Order By: Relevance
“…The quality of food is significantly influenced by its texture, and research has demonstrated that TS can enhance the texture of food items [ 68 ]. In a study conducted by Peña-Gonzalez et al [ 69 ], beef was subjected to ultrasound treatment with a frequency of 40 kHz and intensity of 11 W/cm 2 for 60 min after being stored for 0, 7, or 14 days.…”
Section: Impact Of Ts On the Quality Of Food Itemsmentioning
confidence: 99%
“…The quality of food is significantly influenced by its texture, and research has demonstrated that TS can enhance the texture of food items [ 68 ]. In a study conducted by Peña-Gonzalez et al [ 69 ], beef was subjected to ultrasound treatment with a frequency of 40 kHz and intensity of 11 W/cm 2 for 60 min after being stored for 0, 7, or 14 days.…”
Section: Impact Of Ts On the Quality Of Food Itemsmentioning
confidence: 99%
“…Bacterial growth has been reported to increase in pork with a higher porosity following ultrasound treatment. Higher porosity Journal of Poultry Science, 60, jpsa.2023027 (2023) promotes oxygen and nutrient transport to the cells, which influences the growth of bacteria [30]. In this study, the rate of bacterial growth did not differ significantly between SAEW-treated or untreated samples (Table 3), although it correlated positively with porosity.…”
mentioning
confidence: 56%
“…Various methods of curing have been examined to ascertain their impact on different quality parameters. Vacuum tumbling curing results in reduced oxidation of proteins and lipids, increased α-helix structure, and developed meat products' sensory characteristics [16]. Ultrasonic brining leads to a decreasing sodium level and an E. coli infection during meat processing [17].…”
Section: Brine Curingmentioning
confidence: 99%